Utilizing Tiktok as an Alternative Media for Learning History among General Z - Jas Ryanata Sukma; Urwatul Wusqo; Nensi Lingga Ananda; Safatul Jannah (Journal of English Language and Education, 2026)
The development of digital technology demands innovation in history learning to suit the characteristics of Generation Z, who tend to be visual, interactive, and familiar with social media. One platform that has the potential to be used as an alternative medium for history learning is TikTok. This study aims to analyze the use of TikTok in history learning among Generation Z, including the forms of use, the types of historical content preferred, the effectiveness of use, and the challenges faced. This study used a descriptive qualitative approach with an internet search method as a data collection technique through the exploration of relevant digital sources. The results show that TikTok is effective in increasing student interest, motivation, and engagement through short, narrative, visual, and contextual historical content. However, its use still faces challenges such as limited video length, the risk of material simplification, the potential for distortion of historical facts, and limited digital competence of educators. Therefore, pedagogical planning, digital literacy, and policy support are needed so that TikTok can be used educationally and responsibly.